DAMPAK VOLATILITAS NILAI TUKAR DAN STRATEGI HEDGING TERHADAP MANAJEMEN RISIKO KEUANGAN DI PERUSAHAAN EKSPOR: STUDI KASUS DAN TEORI MANAJEMEN RISIKO DALAM EKONOMI GLOBAL - Iswanto Iswanto; Raden Hebat Kurnia; Wina Sari Asmara (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to analyse the effect of exchange rate volatility and the effectiveness of hedging strategies on financial risk management in export companies in the context of a global economy full of uncertainty. This study uses library research methods by examining academic literature, empirical data, and modern financial theory to understand the relationship between exchange rate fluctuations, hedging instruments, and corporate financial stability. The results of the analysis show that exchange rate volatility has a direct impact on cash flow, net profit, and corporate capital structure, thereby increasing the urgency of implementing comprehensive risk management policies. Hedging strategies, whether through derivative instruments such as forwards, futures, and options or through a natural hedge approach, have been proven to reduce risk exposure and stabilise financial performance. The effectiveness of hedging greatly depends on the accuracy of instrument selection, market analysis capabilities, policy implementation timing, and corporate governance quality. This study emphasises that the integration of risk management theory and strategic financial practices is an important foundation for export companies in maintaining financial resilience and competitiveness amid volatile global economic dynamics.